Die/Dye : a liminal mediation between nature and industry in a changing industrial Silverton context - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2022)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2021.